Golden Opportunities: Plasmonic Gold Nanostructures for Biomedical Applications based on the Second Near‐Infrared Window. Issue 3 (3rd March 2017) - Park, Jeong‐Eun; Kim, Minho; Hwang, Jae‐Ho; Nam, Jwa‐Min
Abstract : For biomedical applications, the NIR‐II window provides several advantages over the conventional NIR‐I window, including deeper penetration depth, low autofluorescence, and higher value of maximum permissible exposure to laser power. An overview of recently reported NIR‐II‐window‐responsive plasmonic gold nanostructures is presented, and the opportunities, challenges, and future directions for these nanostructures in biomedical research fields are discussed.